Biosensor electrodes prepared by physical vapor deposition

CN109689881BActive Publication Date: 2026-10-27EASTMAN CHEM CO
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN201780056908.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-09-16
Filing Date
2017-08-30
Publication Date
2026-10-27
Estimated Expiration
2037-08-30

Smart Images

  • Figure CN109689881B_ABST
    Figure CN109689881B_ABST
Patent Text Reader

Abstract

A biosensor assembly is provided that provides enhanced properties for a biosensor, such as a blood glucose sensor. The biosensor assembly includes a substrate, a conductive layer deposited on the substrate, and a layer of a resistive material deposited on the conductive layer. The conductive layer includes nickel and chromium such that the combined weight percent of nickel and chromium in the conductive layer is 50 to 100 weight percent, wherein the weight percent of nickel in the conductive layer is greater than 20 weight percent or wherein the thickness of the resistive layer is less than 20 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Background of the Invention . Technical Field

[0002] This invention generally relates to electrodes, such as physical vapor deposition assemblies for electrodes, like those present in biosensors. More particularly, this invention relates to electrodes formed of non-precious metal alloys, such as those present in biosensor assemblies.

[0003] Related technical descriptions Biosensors used to analyze biological samples are becoming increasingly common. For example, with the increase in diabetes cases among the world's population, the need for biosensors to measure blood glucose levels has increased dramatically. Such biosensors are commonly referred to as blood glucose meters and operate by having the user place a drop of blood onto a test strip associated with the meter. The test strip is configured to react to the amount of glucose in the blood drop, allowing the blood glucose meter to detect and display the user's blood glucose level.

[0004] Test strips for biosensors used in blood glucose meters typically consist of two or more electrodes (e.g., a working electrode and a counter electrode) formed on a substrate. Furthermore, bioreactants that react with the biological sample, such as enzymes (e.g., glucose oxidase, glucose dehydrogenase, etc.), and mediators (e.g., ferricyanides, ruthenium complexes, osmium complexes, quinones, phenothiazines, phenothiazines, etc.), are formed on one or both electrodes (e.g., the working electrode). In the operation of a blood glucose meter-type biosensor, a drop of blood is applied to the test strip. Subsequently, an electrochemical reaction occurs on the working electrode, proportional to the amount of glucose in the blood. More specifically, glucose first reacts with bioreactants, such as enzymes (glucose oxidase, glucose dehydrogenase, etc.), and sometimes enzyme cofactors (PQQ, FAD, etc.), and is oxidized to gluconic acid. This bioreactant—e.g., enzyme, cofactor, or enzyme-cofactor complex—is temporarily reduced by two electrons transferred from glucose to the enzyme, cofactor, or enzyme-cofactor complex. Next, the reduced bioreactant (e.g., an enzyme, cofactor, or enzyme-cofactor complex) reacts with the mediator, transferring a single electron to each of the two mediator classes (molecules or complexes) in a single-electron reduction process. When the mediator class is reduced, the enzyme, cofactor, or enzyme-cofactor complex thus returns to its original oxidation state. Subsequently, the reduced mediator diffuses to the electrode surface, where a predetermined and sufficiently oxidizing potential is applied to the biosensor, causing the reduced mediator to be oxidized back to its original oxidation state. The current generated by the oxidation of the mediator class by the biosensor is measured and is proportional to the amount of glucose in the blood.

[0005] The quality of the working electrode plays a crucial role in the accurate measurement of blood glucose levels. Specifically, the reproducibility of the electrode's electroactive surface area, the batch-reproducibility of the electron transfer kinetics of the electrode in a specific glucose measurement setup, and the long-term stability of the electrode material during storage are all factors that contribute to the accuracy of blood glucose test strips when the electrochemical signal generated by the electrode during measurement is performed. In particular, it is important to minimize the electronic signal generated by the electrode's electrical activity to prevent bias or noise in the measurement and analysis of biological samples. This is typically achieved by using electrode materials that are inherently thermodynamically inert, such as gold, palladium, platinum, iridium, etc. Therefore, most current blood glucose meters use electrodes formed from a substrate coated with palladium, gold, or other precious metals (usually in the purest form commercially available) as the working electrode, and for ease of manufacture, they are often used as the counter electrode or a combination of counter and reference electrodes. These precious metals have minimal reactivity with interfering substances, thereby providing improved chemical resistance for consistent and accurate measurements. However, the cost of using such precious metals in electrodes can be prohibitive.

[0006] Experiments have been conducted using electrodes formed from non-precious metals to reduce the manufacturing cost of biosensors. However, the electrochemical responses (e.g., dose responses) of such non-precious metal electrodes typically deviate significantly from those of electrodes formed from precious metals. Non-precious materials generally lack sufficient anodic stability for use in electrochemical test strips due to the high background current generated when operating at the typical voltages of biosensors. Furthermore, non-precious materials typically lack readily available heteroelectron transfer with the desired analyte. Therefore, electrodes formed from non-precious metals are generally insufficient as direct replacements for precious metals in test strips for many types of biosensors. Besides low electrochemical response, sufficient electron transfer kinetics with mediators are equally desirable for biosensor electrodes. While some proposed non-precious metals exhibit relatively low electrochemical responses (or reasonable anodic stability), they still lack acceptable electron transfer kinetics with mediators.

[0007] Therefore, there is a need for electrodes that can provide consistent and accurate measurements while offering a cost-effective alternative to the use of precious metals, such as in biosensors. In particular, there is a need for electrodes formed from non-precious metal alloys that can be used in biosensor assemblies for consistent and accurate measurement of biological samples. Invention Overview It has been found that non-precious metals undergo aging upon exposure to atmospheric conditions, leading to altered performance in biosensor applications. It has also been found that electrodes formed by depositing non-precious metals on a substrate membrane to create a conductive layer can be significantly improved by depositing a thin layer of resistive material on the conductive layer for biosensor applications. Furthermore, it has been found that electrodes formed by depositing non-precious metals on a substrate membrane require sufficient mechanical robustness to achieve adequate performance for biosensor applications. Therefore, there is a need for electrodes formed from non-precious metal alloys that can be used in biosensor components for consistent and accurate measurement of biological samples, and that possess good mechanical robustness to allow for fabrication and to achieve or maintain electrical properties.

[0009] One or more embodiments of this disclosure may relate to an electrode that may comprise a substrate, at least one non-precious metal alloy conductive layer deposited on the substrate, and at least one resistive material layer deposited on the non-precious metal layer. The conductive layer may comprise nickel and chromium, wherein the combined weight percentage of nickel and chromium in the conductive layer is at least about 50% by weight of the total weight of the conductive layer.

[0010] In some embodiments, the conductive layer may comprise nickel and chromium, wherein the combined weight percentage of nickel and chromium in the conductive layer may be at least 60, 70, 80, 90, or 95% by weight of the total weight of the conductive layer. In one embodiment, the thickness of the resistive material layer is less than 20 nm. In some embodiments, the conductive layer may comprise nickel in an amount less than 80% by weight of the total weight of the conductive layer and chromium in an amount greater than 20% by weight of the total weight of the conductive layer. While most of this disclosure relates to electrodes used as biosensor components, it is contemplated that the electrodes may also be used in other end-use applications. As a result, any disclosure herein relating to electrodes for use in biosensors is intended to apply to all electrodes to which the technology can be reasonably applied by those skilled in the art.

[0011] In a first aspect, the conductive layer may comprise nickel and chromium, wherein the combined weight percentage of nickel and chromium in the conductive layer may be at least 50, at least 60, at least 70, at least 80, at least 90, or at least 95% of the total weight of the conductive layer equal to 100% by weight, and the thickness of the resistive material layer is less than 20 nm, wherein the combined weight percentage of nickel and chromium in the conductive layer is 90 to 100% by weight, and wherein the thickness of the resistive layer is 5 to 15 nm.

[0012] In an embodiment of the first aspect, the resistive material layer comprises amorphous carbon. In some embodiments, the resistive material layer is amorphous carbon deposited by sputtering. In some embodiments, the resistive material layer is amorphous carbon deposited by sputtering using a solid carbon source.

[0013] In an embodiment of the first aspect, the resistive material layer comprises amorphous carbon, the conductive layer contains chromium at a weight percentage of about 25 to about 95% by weight, and the balance of the conductive layer is substantially nickel.

[0014] In an embodiment of the first aspect, the resistive material layer comprises amorphous carbon, the conductive layer contains chromium at a weight percentage greater than 50% to about 95% by weight, and the balance of the conductive layer is substantially nickel.

[0015] In an embodiment of the first aspect, the resistive material layer comprises amorphous carbon and has a thickness of 5 to 15 nm.

[0016] In a second aspect, the conductive layer may comprise nickel and chromium, wherein the combined weight percentage of nickel and chromium in the conductive layer may be at least 50, at least 60, at least 70, at least 80, at least 90, or at least 95% by weight, equal to 100% by weight of the total weight of the conductive layer, and wherein the conductive layer comprises more than 20% by weight of chromium, equal to 100% by weight of the total weight of the conductive layer. In an embodiment of the second aspect, the substrate has a thickness of 25 to 500 µm, the conductive layer has a thickness of 15 to 200 nm, and the resistive material layer has a thickness of 5 to 200 nm or 5 to 100 nm.

[0017] In an embodiment of the second aspect, based on a total weight of 100% by weight of the conductive layer, the conductive layer may contain less than 80% by weight or less than 75% by weight of nickel and more than 20% by weight or more than 25% by weight of chromium, and wherein the total combined weight percentage of nickel and chromium in the conductive layer is 90 to 100% or 95 to 100% by weight.

[0018] In an embodiment of the second aspect, the conductive layer contains approximately 25% to approximately 95% chromium by weight, and the balance of the conductive layer is substantially nickel. In another embodiment of the second aspect, the conductive layer contains approximately 30% to approximately 95% chromium by weight, and the balance of the conductive layer is substantially nickel. In a further embodiment of the second aspect, the conductive layer contains approximately 40% to approximately 95% chromium by weight, and the balance of the conductive layer is substantially nickel. In yet another embodiment of the second aspect, the conductive layer contains approximately 50% to approximately 95% chromium by weight, and the balance of the conductive layer is substantially nickel. In yet another embodiment of the second aspect, the conductive layer contains more than 50% to approximately 95% chromium by weight, and the balance of the conductive layer is substantially nickel.

[0019] In an embodiment of the second aspect, the resistive layer is amorphous carbon. In one embodiment of the second aspect, the resistive layer is amorphous carbon, the conductive layer contains approximately 25% to approximately 95% chromium by weight, and the balance of the conductive layer is substantially nickel. In another embodiment of the second aspect, the resistive layer is amorphous carbon, the conductive layer contains greater than 50% to approximately 95% chromium by weight, and the balance of the conductive layer is substantially nickel. In an embodiment of the second aspect, the resistive layer is amorphous carbon, and the resistive material layer has a thickness of 5 to 30 nm or 5 to 20 nm.

[0020] In some embodiments of this disclosure, the conductive layer may be coated onto the substrate by physical vapor deposition, the substrate being composed of at least one of any polymers described in the art and / or herein, including but not limited to polycarbonate, silicone polymers, acrylics, PET, modified PET such as PETG or PCTG, PCT, modified PCT, polyesters containing TMCD and CHDM, PCCD, or PEN.

[0021] In a particular embodiment of this disclosure, the resistive material layer may comprise a thin film of resistive material deposited on the surface of the conductive layer. The term "resistive material" refers to a material that is more resistive than the conductive layer, allowing current to flow when a constant potential is applied, and, when formed into a thin-film electrode having a conductive layer and a resistive material layer on the conductive layer, improves the anodic stability and / or electron transfer kinetics of the electrode compared to a similar electrode having only a conductive layer, as determined by a type 1 linear sweep voltammetry test.

[0022] In some embodiments, the resistive material layer may comprise one or more elements selected from carbon, silicon, boron, oxygen, and combinations thereof. In some embodiments, the resistive material layer comprises carbon. In some embodiments, the resistive material layer comprises amorphous carbon. In some embodiments, the resistive material layer is amorphous carbon deposited by sputtering. In some embodiments, the resistive material layer is amorphous carbon deposited by sputtering using a carbon source. In some embodiments, the resistive material layer is amorphous carbon deposited by sputtering using a carbon source in a separate sputtering step different from the sputtering step used to deposit the conductive layer (i.e., no co-sputtering of the conductive layer and the carbon layer is performed).

[0023] In some embodiments, the resistive layer comprises mainly sp 2 Hybridized carbon, sp 3 Amorphous carbon composed of hybrid carbon or combinations thereof. In some embodiments, it is mainly composed of sp... 2 Hybridized carbon, sp 3Amorphous carbon layers composed of hybrid carbon or combinations thereof can be formed using the following techniques / processes: Onoprienko, AA, Shaginyan, LR, Role of microstructure in forming thin carbon film properties. Diamond Relat. Mater. 1994, 3, 1132-1136; Onoprienko, A., In Carbon, The Future Material for Advanced Technology Applications; Messina, G., Santangelo, S., Eds.; Springer Berlin Heidelberg, 2006; or Cho, NH; Krishnan, KM; Veirs, DK; Rubin, MD; Hopper, CB; Bhushan, B.; Bogy, DB. Chemical structure and physical properties of diamond-like amorphous carbon films prepared by magnetron sputtering. J. Mater. Res. 1990, 5, 2543-2554.

[0024] In some embodiments of this disclosure, the resistive material layer may have a thickness of 5 to 200 nm, the conductive layer may have a thickness of 15 to 200 nm, and the substrate may have a thickness of 25 to 500 µm. In some embodiments, the resistive material layer may have a thickness of 5 to less than 20 nm, the conductive layer may have a thickness of 15 to 200 nm, and the substrate may have a thickness of 25 to 500 µm. In some embodiments, the biosensor assembly may also have a visible light transmittance of no more than 20%, or no more than 15%, or no more than 10%, or no more than 5%, or 0.01 to 20%, or 0.01 to 15%, or 0.01 to 10%, or 0.01 to 5% as measured by ASTM D1003.

[0025] In some embodiments of this disclosure, the resistive material layer may have a thickness of 5 to 200 nm or 5 to less than 20 nm, the conductive layer may have a thickness of 15 to 200 nm, and the substrate may have a thickness of 25 to 500 µm, wherein the biosensor assembly has a visible light transmittance of no more than 20%.

[0026] In some embodiments of this disclosure, the resistive material layer may have a thickness of 5 to 200 nm or 5 to less than 20 nm, the conductive layer may have a thickness of 15 to 200 nm, and the substrate may have a thickness of 25 to 500 µm, wherein the biosensor assembly has a visible light transmittance of no more than 15%.

[0027] In some embodiments of this disclosure, the resistive material layer may have a thickness of 5 to 200 nm or 5 to less than 20 nm, the conductive layer may have a thickness of 15 to 200 nm, and the substrate may have a thickness of 25 to 500 µm, wherein the biosensor assembly has a visible light transmittance of no more than 10%.

[0028] In some embodiments of this disclosure, the resistive material layer may have a thickness of 5 to 200 nm or 5 to less than 20 nm, the conductive layer may have a thickness of 15 to 200 nm, and the substrate may have a thickness of 25 to 500 µm, wherein the biosensor assembly has a visible light transmittance of no more than 5%.

[0029] In some embodiments, the resistive material layer has a thickness of 5 to 100 nm, or 5 to 50 nm, or 5 to 30 nm, or 5 to 25 nm, or 5 to 20 nm, or 5 to less than 20 nm, or 5 to 15 nm. In some embodiments, the resistive material layer is amorphous carbon and has a thickness of 5 to 100 nm, or 5 to 50 nm, or 5 to 30 nm, or 5 to 25 nm, or 5 to 20 nm, or 5 to less than 20 nm, or 5 to 15 nm. In some embodiments, the resistive material layer is amorphous carbon and has a thickness of 5 to 20 nm, or 5 to less than 20 nm, or 5 to 15 nm.

[0030] In one aspect, certain embodiments of this disclosure relate to a biosensor assembly comprising a substrate, a conductive layer deposited on the substrate, and a resistive material layer deposited on the conductive layer, wherein the resistive material layer may contain carbon, and based on 100% by weight of the total weight of the conductive layer, the conductive layer may contain nickel and chromium in a combined weight of 50% to 100% by weight, with the amount of chromium being greater than 20% by weight and the amount of nickel being less than 80% by weight, and the substrate may consist of at least one of any polymers described in the art and / or herein, including but not limited to polycarbonate, silicone polymers, acrylics, PET, modified PET such as PETG or PCTG, PCT, PCTA, polyesters containing TMCD and CHDM, PCCD, or PEN, obtained by any method known in the art, including but not limited to physical vapor deposition. The resistive layer may have a thickness of 5 to 100 nm, or 5 to less than 20 nm, the conductive layer may have a thickness of 15 to 200 nm, and the substrate may have a thickness of 25 to 500 µm, so that the biosensor assembly has a visible light transmittance of no more than 20%, or no more than 15%, or no more than 10%, or no more than 5%.

[0031] In one aspect, certain embodiments of this disclosure relate to a biosensor assembly comprising a substrate, a conductive layer deposited on the substrate, and a resistive material layer deposited on the conductive layer, wherein the resistive material layer may contain carbon, and based on 100% by weight of the total weight of the conductive layer, the conductive layer may contain nickel and chromium in a combined weight of at least 50, or at least 60, or at least 70, or at least 80, or at least 90, or at least 95% by weight, the thickness of the resistive material layer is less than 20 nm, and the substrate may consist of at least one of any polymers described in the art and / or herein, including but not limited to polycarbonate, silicone polymers, acrylics, PET, modified PET such as PETG or PCTG, PCT, PCTA, polyesters containing TMCD and CHDM, PCCD, or PEN, obtained by any method known in the art, including but not limited to physical vapor deposition. The resistive layer may have a thickness of 5 to less than 20 nm, or 5 to 15 nm, the conductive layer may have a thickness of 15 to 200 nm, and the substrate may have a thickness of 25 to 500 µm, so that the biosensor assembly has a visible light transmittance of no more than 20%, or no more than 15%, or no more than 10%, or no more than 5%.

[0032] One or more embodiments of this disclosure may relate to electrodes for use in biosensors, wherein the electrode includes a substrate, a conductive layer deposited on the substrate, and a resistive material layer deposited on the conductive layer. In some embodiments, the conductive layer may comprise nickel and chromium, and the conductive layer may have an oxidation voltage (hereinafter referred to as E) of less than 450, or less than 400, or less than 375, or less than 350, or less than 325, or less than 300, or less than 275 mV for the Fe(II)[CN]6 mediator, as determined by a type I linear scan voltammetry test (as described in the Examples section). 峰值,阳极 ).

[0033] The substrate may consist of any polymer composition known in the art, including but not limited to at least one polymer selected from: nylon, polyester, copolyester, polyethylene, polypropylene, polyamide; polystyrene, polystyrene copolymer, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer, poly(methyl methacrylate), acrylic copolymer, poly(ether-imide); polyphenylene ether or poly(phenylene ether) / polystyrene blend, polystyrene resin; polyphenylene sulfide; polyphenylene sulfide / sulfone; poly(ester-carbonate); polycarbonate; polysulfone; polysulfone ether; and poly(ether-ketone); or any other mixture of the foregoing polymers.

[0034] In one embodiment, the substrate may be composed of at least one polyester containing residues of at least one diol selected from ethylene glycol, 1,4-cyclohexanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol.

[0035] In one embodiment, the substrate may be composed of at least one polyester comprising residues of terephthalic acid and / or dimethyl terephthalate and residues of at least one diol selected from ethylene glycol, 1,4-cyclohexanediol and 2,2,4,4-tetramethyl-1,3-cyclobutanediol.

[0036] In one embodiment, the substrate may be composed of at least one polyester comprising an acid component containing residues of terephthalic acid and isophthalic acid and / or their esters such as dimethyl terephthalate, and a diol component containing residues of at least one diol selected from ethylene glycol residues, 1,4-cyclohexanediethanol residues and 2,2,4,4-tetramethyl-1,3-cyclobutanediol.

[0037] In one embodiment, the substrate may consist of at least one polyester comprising terephthalic acid residues or esters thereof, or mixtures thereof, and 1,4-cyclohexanediethanol residues.

[0038] In one embodiment, the substrate may consist of at least one polyester made from terephthalic acid residues or esters thereof, or mixtures thereof, and 1,4-cyclohexanediethanol residues and / or 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues.

[0039] In one embodiment, the substrate may consist of at least one polyester made from terephthalic acid residues or esters thereof, or mixtures thereof, 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues and 1,4-cyclohexanediethanol residues.

[0040] In one embodiment, the substrate may consist of at least one polyester made from terephthalic acid residues or esters thereof, or mixtures thereof, 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues and ethylene glycol residues.

[0041] In one embodiment, the substrate may consist of at least one polyester made from terephthalic acid residues or esters thereof, or mixtures thereof, ethylene glycol residues and 1,4-cyclohexanediethanol residues.

[0042] The conductive layer in this disclosure may consist of a single layer comprising any alloy composition disclosed in this application. In some embodiments, the alloy composition contains an alloy that may be a solid solution (single phase) of an element, a mixture of metallic phases (two or more solutions), or an intermetallic compound in which there are no clear boundaries between the phases.

[0043] One or more embodiments of this disclosure relate to a method of forming an electrode for a biosensor. The method includes (a) providing a substrate; (b) providing a conductive layer target; (c) performing a material physical vapor deposition of at least a portion of the substrate from the conductive layer target to thereby form a conductive layer on the substrate, the conductive layer having a conductive layer surface facing the opposite side of the substrate; (d) providing a target that generates a resistive material when used as a source material for physical vapor deposition, the target being referred to hereinafter as a "resistive material target"; and (e) performing a material physical vapor deposition of at least a portion of the conductive layer from the resistive material target to thereby form a resistive material layer on the conductive layer surface. The conductive material may comprise nickel and chromium, wherein the combined weight percentage of nickel and chromium in the conductive layer may be at least 50, or at least 60, or at least 70, or at least 80, or at least 90, or at least 95% by weight. In some embodiments, the resistive material layer may comprise amorphous carbon and have a thickness of 5 to 100 nm, or 5 to 50 nm, or 5 to 25 nm, or 5 to less than 20 nm. In one embodiment, the resistive material layer may comprise amorphous carbon and have a thickness of 5 to less than 20 nm. In another embodiment, the conductive material may comprise nickel and chromium, wherein the chromium is present in an amount greater than 20% by weight, or at least 25% by weight, and the resistive material layer may comprise amorphous carbon and have a thickness of 5 to 100 nm. Furthermore, the combined conductive and resistive material layers may have a sheet resistance of less than 2000 ohms / square.

[0044] One or more embodiments of this disclosure relate to a method of forming electrodes for a biosensor. The combined conductive and resistive material layers may have a sheet resistance of no more than 5000, 2000, 100, 80, 60, 50, 40, 20, 10, or 5 ohms / square, as measured by ASTM F1711-96. In some embodiments, the layer has a sheet resistance of 1 to 5000 ohms / square, 1 to 4000 ohms / square, 1 to 3000 ohms / square, 1 to 2000 ohms / square, 1 to 1000 ohms / square, 1 to 500 ohms / square, 5 to 100 ohms / square, 5 to 20 ohms / square, 5 to 15 ohms / square, 5 to 10 ohms / square, 10 to 80 ohms / square, 20 to 60 ohms / square, or 40 to 50 ohms / square, as measured by ASTM F1711-96. This layer can have a sheet resistance of less than 2000 ohms / square.

[0045] Overview of the attached figures Embodiments of this disclosure are described herein with reference to the following figures, wherein: Figure 1 This is a cross-sectional schematic diagram of a thin-film electrode biosensor assembly according to an embodiment of this disclosure; Figure 2 This is a schematic diagram of the biosensor assembly of the test strip according to the embodiment of this disclosure; Figure 3 It is a graph depicting the linear scan voltammetry of a thin-film electrode in a solution containing a mediator; Figure 4 This is a graph depicting linear sweep voltammetry of thin-film electrodes with various carbon-coated NiCr metal alloy conductive layers in a buffer solution containing Fe(II)[CN]6 mediator. Figure 5 It is the average E of various NiCr metal alloy conductive layers covered with carbon in a buffer solution containing Fe(II)[CN]6 mediator. 峰值,阳极 Value graph; Figure 6 This is a graph depicting linear scan voltammetry plots of thin film electrodes with carbon-coated NiCr metal alloy conductive layers containing 40 and 80 wt% Ni, respectively, in a buffer solution containing Fe(II)[CN]6 mediator. Figure 7 It is a graph depicting the effect of bending thin film electrodes on the thin film resistance of various NiCr conductive layer alloys covered with carbon on mandrels (coated surface contacts) of various diameters. Invention Details This invention generally relates to components for electrodes, such as those used in biosensors. The term "biosensor" as used herein should refer to a device for analyzing biological samples. In some embodiments, such as... Figure 1 As shown, the biosensor assembly may be a layered thin-film electrode 100 and may generally include a substrate 102, a conductive layer 104 deposited on at least a portion of the substrate 102, and a resistive material layer 106 deposited on at least a portion of the conductive layer 104. In some embodiments, the biosensor may be a medical sensor, such as a glucose measurement system, and the biosensor assembly may be a test strip used with the biosensor. The term "medical sensor" as used herein should refer to a biosensor used for medical monitoring and / or diagnosis. For example, such as... Figure 2 As shown, some embodiments suggest that the biosensor assembly includes a test strip 110, which includes a first electrode 100 separated from a second electrode 100a by a reaction space 112. The first electrode 100 may include a working electrode, and the second electrode 100a may include a reference electrode, a counter electrode, or a combination of a reference electrode and a counter electrode. Therefore, a biological sample, such as a drop of blood, can be placed in the reaction space 112 and electrically contacted with the first and second electrodes 100 and 100a for analysis. It should be understood that... Figure 2This is not intended to be limiting and illustrates one possible implementation of the test strip. Other implementations of the test strip may include different configurations of electrodes, such as coplanar electrode configurations. As used herein, the term "glucose sensor" should refer to a medical sensor used to determine the concentration of glucose in the blood. Furthermore, bioreactive substances that react with biological samples, such as proteins, enzymes (e.g., glucose oxidase, glucose dehydrogenase, etc.), and mediators (e.g., ferricyanides, ruthenium complexes, osmium complexes, quinones, phenothiazines, phenoxazines, etc.), may be formed on one or two electrodes, such as the working electrode.

[0047] Unlike conventional physical vapor deposition biosensor assemblies that typically include and / or utilize precious metals such as palladium and / or gold, the biosensor assemblies described herein can be formed from non-precious metal alloys, such as those including nickel and chromium. However, biosensor assemblies formed from non-precious metal alloys, such as thin-film electrodes, with a resistive material layer deposited thereon, as described herein, can exhibit excellent consistency and accuracy when measuring biological samples. Thus, by using biosensor assemblies composed of non-precious metal alloys and resistive material layers as described herein, the material and manufacturing costs typically associated with the fabrication and use of biosensor assemblies can be significantly reduced.

[0048] Embodiments of this disclosure provide a substrate 102 formed of any type of material (flexible or rigid) that is generally non-conductive and chemically inert to the intended chemical reactions described herein. In some embodiments, the substrate 102 of the biosensor assembly may comprise a flexible, non-conductive membrane comprising a polymer, such as a polymer membrane, polyester membrane, polycarbonate membrane, etc. In some specific embodiments, the substrate 102 may comprise a polyethylene terephthalate (PET) membrane. Embodiments of this disclosure suggest that the substrate 102 may have a thickness of at least 25 µm, 125 µm, or 250 µm and / or no greater than 800 µm, 500 µm, or 400 µm. In some embodiments, the substrate 102 may have a thickness of 25 to 800 µm, 25 to 500 µm, or 25 to 400 µm, 125 to 800 µm, 125 to 500 µm, or 125 to 400 µm, or 250 to 800 µm, 250 to 500 µm, or 250 to 400 µm.

[0049] The conductive layer 104 coated on the substrate 102 may contain one or more non-noble metals. This conductive layer 104 may be coated on the substrate 102 via one or more physical vapor deposition techniques, such as sputtering (e.g., magnetron sputtering, unbalanced magnetron sputtering, directed-target sputtering, etc.), thermal evaporation, electron beam evaporation, laser ablation, arc vaporization, co-evaporation, ion plating, etc. The conductive layer 104 may be coated on the substrate 102 to a thickness of at least 1, 10, 15, or 30 nm and / or no greater than 1000, 200, 100, or 50 nm. In some embodiments, the conductive layer 104 may have a thickness of 1 to 1000 nm, 1 to 200 nm, 1 to 100 nm, or 1 to 50 nm, 10 to 1000 nm, 10 to 200 nm, 10 to 100 nm, or 10 to 50 nm, 15 to 1000 nm, 15 to 200 nm, 15 to 100 nm, or 15 to 50 nm, or 30 to 1000 nm, 30 to 200 nm, 30 to 100 nm, or 30 to 50 nm.

[0050] The resistive material layer 106 can be deposited on the conductive layer 104 via one or more physical vapor deposition techniques, such as sputtering (e.g., magnetron sputtering, unbalanced magnetron sputtering, directed target sputtering, etc.), thermal evaporation, electron beam evaporation, arc vaporization, co-evaporation, ion plating, plasma-enhanced vapor deposition, atomic layer deposition, etc. In some embodiments, the resistive material layer 106 can be coated on the substrate 104 to an amount of at least 1, 5, 10, or 15 nm and / or no greater than 200, 100, 50, 25, 20, less than 20, or a thickness of 15 nm. In some embodiments, the resistive layer 106 may have a thickness of 1 to 200 nm, 1 to 100 nm, 1 to 50 nm, 1 to 20 nm, 1 to less than 20 nm, or 1 to 15 nm; or 5 to 200 nm, 5 to 100 nm, 5 to 50 nm, 5 to 25 nm, 5 to less than 20 nm, or 5 to 15 nm; or 10 to 200 nm, 10 to 100 nm, 10 to 50 nm, or 10 to 25 nm, 10 to 20 nm, 10 to less than 20 nm, or 10 to 15 nm. In the embodiments, the resistive layer 106 may have a thickness of 1 to less than 20 nm, or 1 to 19 nm, or 1 to 18 nm, or 1 to 17 nm, or 1 to 16 nm, or 5 to 19 nm, or 5 to 18 nm, or 5 to 17 nm, or 5 to 16 nm, or 7 to 19 nm, or 7 to 18 nm, or 7 to 17 nm, or 7 to 16 nm, or 10 to 19 nm, or 10 to 18 nm, or 10 to 17 nm, or 10 to 16 nm.

[0051] The conductive layer 104 and the resistive material layer 106 may be deposited on the substrate 102 such that the resulting thin-film electrode 100 is generally opaque to visible light. For example, the resulting thin-film electrode 100 may have a visible light transmittance of no more than 50%, no more than 40%, no more than 30%, or no more than 20% as measured by ASTM D1003. In some embodiments, the resulting thin-film electrode 100 may have a visible light transmittance of 1 to 50%, 10 to 40%, 15 to 30%, or about 20%. Furthermore, the resulting thin-film electrode 100 may have a sheet resistance of no more than 5000, 2000, 100, 80, 60, 50, 40, 20, 10, or 5 ohms / square as measured by ASTM F1711-96. In some embodiments, the resulting thin-film electrode 100 may have a sheet resistance of 1 to 5000 ohms / square, 2 to 2000 ohms / square, 5 to 100 ohms / square, 10 to 80 ohms / square, 20 to 60 ohms / square, or 40 to 50 ohms / square.

[0052] The non-noble metal described herein that forms the conductive layer 104 can be composed of an alloy of nickel and chromium. For example, the conductive layer 104 of the biosensor assembly is prepared using a non-noble metal alloy consisting of at least 5% by weight of nickel and at least 5% by weight of chromium, wherein the conductive layer is further coated by depositing an amorphous carbon resistive material layer 106 on the conductive layer 104. Electrodes comprising the conductive layer and the amorphous carbon resistive material layer are prepared using various alloys containing nickel and chromium in a Ni:Cr (weight) ratio of 100:0 to 0:100.

[0053] In some embodiments, the amount of nickel and chromium contained in the non-precious metal alloy constituting the conductive layer of the electrode (e.g., conductive layer 104 of a biosensor assembly) can vary depending on the specific requirements of the electrode, such as the biosensor assembly. In various embodiments, the non-precious metal alloy may contain at least about 5% to about 95% by weight of nickel. Furthermore, in various embodiments, the non-precious metal alloy may contain at least about 5%, 10%, 20%, greater than 20%, 25%, 30%, 40%, 50%, or greater than 50%, 60%, and / or up to about 95%, 90%, 80%, 70%, 60%, greater than 50%, 50%, or 40% by weight of chromium. More specifically, in the embodiments, the non-precious metal alloy may contain approximately 5 to 95, 10 to 90, 10 to 80, 10 to 70, 10 to 60, 10 to 50, 10 to 40, 20 to 90, 20 to 80, 20 to 70, 20 to 60, 20 to 50, 20 to 40, greater than 20 to 90, greater than 20 to 80, greater than 20 to 70, greater than 20 to 60, greater than 20 to 50, greater than 20 to 40, 25 to 90, 25 to 80, 25 to 70, 25 to 60, 25 to 50, 25 to 40, 30 Chromium content of 90 to 90%, 30 to 80%, 30 to 70%, 30 to 60%, 30 to 50%, 30 to 40%, 40 to 90%, 40 to 80%, 40 to 70%, 40 to 60%, 40 to 50%, 50 to 90%, 50 to 80%, 50 to 70%, 50 to 60%, greater than 50 to 95%, greater than 50 to 90%, greater than 50 to 80%, greater than 50 to 70%, greater than 50 to 60%, 60 to 95%, 60 to 90%, 60 to 80%, 60 to 70%, 70 to 95%, 70 to 90%, 70 to 80%, 80 to 95%, or 80 to 90% by weight. In one embodiment, in addition to the chromium content as described above, the balance of the alloy is nickel. It should be understood that an alloy containing nickel and chromium in a combined amount of 100% by weight may still contain small amounts of other elements as impurities.

[0054] In some embodiments, the amount of nickel and chromium contained in the non-precious metal alloy constituting the conductive layer of the electrode, such as a biosensor component, can be varied according to the specific requirements of the biosensor component as follows: 10 to 95 wt% chromium and 5 to 90 wt% nickel; 10 to 90 wt% chromium and 10 to 90 wt% nickel; or 10 to 80 wt% chromium and 20 to 90 wt% nickel; or 10 to 70 wt% chromium and 30 to 90 wt% nickel; or 10 to 60 wt% chromium and 40 to 90 wt% nickel; or 10 to 50 wt% chromium and 50 to 90 wt% nickel, or 10 to 40 wt% chromium and 60 to 90 wt% nickel; or 20 to 90 wt% chromium and 10 to 80 wt% nickel. ; or 20 to 80 wt% chromium and 20 to 80 wt% nickel; or 20 to 70 wt% chromium and 30 to 80 wt% nickel; or 20 to 60 wt% chromium and 40 to 80 wt% nickel; or 20 to 50 wt% chromium and 50 to 80 wt% nickel; or 20 to 40 wt% chromium and 60 to 80 wt% nickel; or greater than 20 to 90 wt% chromium and 10 to less than 80 wt% nickel; or greater than 20 to 80 wt% chromium and 20 to less than 80 wt% nickel; or greater than 20 to 70 wt% chromium and 30 to less than 80 wt% nickel; or greater than 20 to 60 wt% chromium and 40 to less than 80 wt% nickel; or greater than 20 to 50 wt% chromium and 50 to less than 80 wt% nickel. % by weight of nickel; or greater than 20 to 40 % by weight of chromium and less than 80 % by weight of nickel; or 25 to 90 % by weight of chromium and 10 to 75 % by weight of nickel; or 25 to 80 % by weight of chromium and 20 to 75 % by weight of nickel; or 25 to 70 % by weight of chromium and 30 to 75 % by weight of nickel; or 25 to 60 % by weight of chromium and 40 to 75 % by weight of nickel; or 25 to 50 % by weight of chromium and 50 to 75 % by weight of nickel; or 25 to 40 % by weight of chromium and 60 to 75 % by weight of nickel; or 30 to 90 % by weight of chromium and 10 to 70 % by weight of nickel; or 30 to 80 % by weight of chromium and 20 to 70 % by weight of nickel; or 30 to 60 % by weight of chromium and 3 ... 0% by weight of chromium and 40 to 70% by weight of nickel; or 30 to 50% by weight of chromium and 50 to 70% by weight of nickel; or 30 to 40% by weight of chromium and 60 to 70% by weight of nickel; or 40 to 90% by weight of chromium and 10 to 60% by weight of nickel; or 40 to 80% by weight of chromium and 20 to 60% by weight of nickel; or 40 to 70% by weight of chromium and 30 to 60% by weight of nickel; or 40 to 60% by weight of chromium and 40 to 60% by weight of nickel; or 40 to 50% by weight of chromium and 50 to 60% by weight of nickel; or 50 to 95% by weight of chromium and 5 to 50% by weight of nickel; or 50 to 90% by weight of chromium and 10 to 50% by weight of nickel; or 50 to 80% by weight of chromium and 20 to 50% by weight of nickel;Or 50 to 70% by weight of chromium and 30 to 50% by weight of nickel; or 50 to 60% by weight of chromium and 40 to 50% by weight of nickel; or greater than 50 to 95% by weight of chromium and 5 to less than 50% by weight of nickel; or greater than 50 to 90% by weight of chromium and 10 to less than 50% by weight of nickel; or greater than 50 to 80% by weight of chromium and 20 to less than 50% by weight of nickel; or greater than 50 to 70% by weight of chromium and 30 to less than 50% by weight of nickel; or greater than 50 to 60% by weight of chromium and 40 to less than 50% by weight of nickel; or 60 to 95% by weight of chromium and 5 to 40% by weight of nickel; or 60 to 90% by weight of chromium and 5 to 40% by weight of nickel. Chromium % by weight and nickel 10 to 40 wt% by weight; or 60 to 80 wt% chromium and nickel 20 to 40 wt% by weight; or 60 to 70 wt% chromium and nickel 30 to 40 wt% by weight; or 70 to 95 wt% chromium and nickel 5 to 30 wt% by weight; or 70 to 90 wt% chromium and nickel 10 to 30 wt% by weight; or 70 to 80 wt% chromium and nickel 20 to 30 wt% by weight; or 80 to 95 wt% chromium and nickel 5 to 20 wt% by weight; or 80 to 90 wt% chromium and nickel 10 to 20 wt% by weight; all these weight percentages are based on a total weight percentage equal to 100 wt% of the conductive layer.

[0055] In some embodiments, the conductive layer contains molybdenum, if present, in an amount of 0 to 2 or 0 to 1% by weight of the total weight of the conductive layer. In some embodiments, the conductive layer contains molybdenum, if present, in an amount of less than 1, less than 0.8, less than 0.6, less than 0.4, less than 0.2, or less than 0.1% by weight of the total weight of the conductive layer. In some embodiments, the conductive layer is substantially molybdenum-free. In some embodiments, the conductive layer is molybdenum-free.

[0056] In some embodiments, the conductive layer contains less than 1.0, or less than 0.5, or less than 0.2% by weight of each of the following elements: iron, carbon, sulfur, phosphorus, molybdenum, niobium, cobalt, aluminum, titanium, or boron. In one embodiment, the conductive layer contains no or substantially no of the following elements: carbon, sulfur, phosphorus, molybdenum, niobium, cobalt, aluminum, titanium, or boron. In some embodiments, the conductive layer comprises nickel and chromium, and contains less than 1.0, or less than 0.5, or less than 0.2, or less than 0.1, or less than 0.05% by weight of any other element. In some embodiments, the conductive layer comprises nickel and chromium, and contains less than 2.0, or less than 1.0, or less than 0.5, or less than 0.2, or less than 0.1, or less than 0.05% by weight of all other element.

[0057] In some embodiments, the amount of nickel and chromium contained in the non-precious metal alloy constituting the conductive layer of the electrode, such as a biosensor component, can be varied according to the specific requirements of the biosensor component as follows: 10 to 95 wt% chromium and 5 to 90 wt% nickel; 10 to 90 wt% chromium and 10 to 90 wt% nickel; or 10 to 80 wt% chromium and 20 to 90 wt% nickel; or 10 to 70 wt% chromium and 30 to 90 wt% nickel; or 10 to 60 wt% chromium and 40 to 90 wt% nickel; or 10 to 50 wt% chromium and 50 to 90 wt% nickel, or 10 to 40 wt% chromium and 60 to 90 wt% nickel; or 20 to 90 wt% chromium and 10 to 80 wt% nickel. ; or 20 to 80 wt% chromium and 20 to 80 wt% nickel; or 20 to 70 wt% chromium and 30 to 80 wt% nickel; or 20 to 60 wt% chromium and 40 to 80 wt% nickel; or 20 to 50 wt% chromium and 50 to 80 wt% nickel; or 20 to 40 wt% chromium and 60 to 80 wt% nickel; or greater than 20 to 90 wt% chromium and 10 to less than 80 wt% nickel; or greater than 20 to 80 wt% chromium and 20 to less than 80 wt% nickel; or greater than 20 to 70 wt% chromium and 30 to less than 80 wt% nickel; or greater than 20 to 60 wt% chromium and 40 to less than 80 wt% nickel; or greater than 20 to 50 wt% chromium and 50 to less than 80 wt% nickel. % by weight of nickel; or greater than 20 to 40 % by weight of chromium and less than 80 % by weight of nickel; or 25 to 90 % by weight of chromium and 10 to 75 % by weight of nickel; or 25 to 80 % by weight of chromium and 20 to 75 % by weight of nickel; or 25 to 70 % by weight of chromium and 30 to 75 % by weight of nickel; or 25 to 60 % by weight of chromium and 40 to 75 % by weight of nickel; or 25 to 50 % by weight of chromium and 50 to 75 % by weight of nickel; or 25 to 40 % by weight of chromium and 60 to 75 % by weight of nickel; or 30 to 90 % by weight of chromium and 10 to 70 % by weight of nickel; or 30 to 80 % by weight of chromium and 20 to 70 % by weight of nickel; or 30 to 60 % by weight of chromium and 3 ... 0% by weight of chromium and 40 to 70% by weight of nickel; or 30 to 50% by weight of chromium and 50 to 70% by weight of nickel; or 30 to 40% by weight of chromium and 60 to 70% by weight of nickel; or 40 to 90% by weight of chromium and 10 to 60% by weight of nickel; or 40 to 80% by weight of chromium and 20 to 60% by weight of nickel; or 40 to 70% by weight of chromium and 30 to 60% by weight of nickel; or 40 to 60% by weight of chromium and 40 to 60% by weight of nickel; or 40 to 50% by weight of chromium and 50 to 60% by weight of nickel; or 50 to 95% by weight of chromium and 5 to 50% by weight of nickel; or 50 to 90% by weight of chromium and 10 to 50% by weight of nickel; or 50 to 80% by weight of chromium and 20 to 50% by weight of nickel;Or 50 to 70% by weight of chromium and 30 to 50% by weight of nickel; or 50 to 60% by weight of chromium and 40 to 50% by weight of nickel; or greater than 50 to 95% by weight of chromium and 5 to less than 50% by weight of nickel; or greater than 50 to 90% by weight of chromium and 10 to less than 50% by weight of nickel; or greater than 50 to 80% by weight of chromium and 20 to less than 50% by weight of nickel; or greater than 50 to 70% by weight of chromium and 30 to less than 50% by weight of nickel; or greater than 50 to 60% by weight of chromium and 40 to less than 50% by weight of nickel; or 60 to 95% by weight of chromium and 5 to 40% by weight of nickel; or 60 to 90% by weight of chromium and 10 to 40% by weight of nickel; or 60 to 80% by weight of chromium and 20 to 40% by weight of nickel. % nickel; or 60 to 70 wt% chromium and 30 to 40 wt% nickel; or 70 to 95 wt% chromium and 5 to 30 wt% nickel; or 70 to 90 wt% chromium and 10 to 30 wt% nickel; or 70 to 80 wt% chromium and 20 to 30 wt% nickel; or 80 to 95 wt% chromium and 5 to 20 wt% nickel; or 80 to 90 wt% chromium and 10 to 20 wt% nickel; all these weight percentages are based on a total weight percentage of 100 wt% of the conductive layer; and wherein the conductive layer comprises nickel and chromium, and contains less than 1.0, or less than 0.5, or less than 0.2 wt% of any other element class, or substantially free of any other element class, or free of any other element class.

[0058] The conductive layer in this disclosure may consist of a single layer comprising any alloy composition disclosed herein. In some embodiments, the alloy composition comprises an alloy that may be a solid solution (single phase) of an element, a mixture of metallic phases (two or more solutions), or an intermetallic compound in which there are no clear boundaries between the phases.

[0059] Those skilled in the art will readily recognize that the elements of this non-precious metal alloy may contain incidental impurities. As used herein, "incidental impurities" refers to any impurities naturally present in the ore used to produce the non-precious metal alloy or unintentionally introduced during the production process. The non-precious metal alloy may contain less than about 0.1, 0.05, or 0.001% by weight of incidental impurities.

[0060] The non-precious metal alloys described herein may also contain one or more additional alloying elements besides those described above. However, in various embodiments, the non-precious metal alloy may be substantially free of such additional alloying elements. The terms "virtually free" and "substantially free" as used herein mean that the non-precious metal alloy contains less than 0.001% by weight of such additional alloying components. Furthermore, the terms "virtually free" and "substantially free" are used interchangeably.

[0061] In some embodiments of this disclosure, the biosensor components described herein can be fabricated by performing the following steps: (a) Provide a base; (b) Provide a conductive layer target; (c) Physical vapor deposition of at least a portion of the substrate using material from the target in order to thereby form a conductive layer on the substrate; (d) Provide a resistive material target; (e) Deposit at least a portion of the conductive layer with material physical vapor from a resistive material target so as to form a resistive material layer on the substrate.

[0062] The substrate provided in step (a) may include any type of substrate material as described above, such as PET. In some embodiments, the substrate comprises a substrate material sheet actuated within a high vacuum chamber. The substrate material sheet may comprise a monolithic material, such as a square sheet. In other embodiments, the substrate material sheet may comprise a roll of material that passes through the high vacuum chamber via a roll-to-roll mechanism, as described in more detail below. In still other embodiments, also as described below, the substrate may remain stationary or be rotatable during the deposition process.

[0063] The provision of the target in step (b) may include providing a physical vapor deposition target composed of any non-precious metal alloy as described above. For example, in some embodiments, a physical vapor deposition target comprising an alloy of nickel and chromium as described herein is used to fabricate a thin film conductive layer. Such alloy targets may contain less than about 0.1, 0.05, or 0.001% by weight of incidental impurities. In some embodiments, the physical vapor deposition target is disposed within and / or contains an electrode, such as a sputtering cathode, during the physical vapor deposition process. In some embodiments, the physical vapor deposition target may be circular, having a diameter of at least 2, 4, 8, 12, 16, or 20 cm. In other embodiments, the physical vapor deposition target may be a tubular target having an inner diameter of at least 2, 4, 8, or 16 cm and an outer diameter of 20, 24, 28, or 32 cm. In still other embodiments, the physical vapor deposition target may be rectangular, having a width of 5 to 25 cm, a length of 25 to 75 cm, and a thickness of 0.3 to 5 cm. However, it should be understood that embodiments of this disclosure consider the use of targets of other shapes and sizes.

[0064] Step (c) of physical vapor deposition typically involves coating a substrate with material from a non-precious metal alloy target to form a conductive layer. As used herein, the term "physical vapor deposition" refers to the deposition of a thin film by condensing vaporized material onto a substrate. Physical vapor deposition coatings can be achieved using any of the aforementioned types of physical vapor deposition methods, i.e., sputtering, thermal evaporation, electron beam evaporation, laser ablation, arc vaporization, co-evaporation, ion plating, etc. For example, in some embodiments, the physical vapor deposition step is performed via sputtering, wherein the substrate is coated with a conductive layer by sputtering a non-precious metal alloy target via a sputtering apparatus. Specific examples of such sputtering-type physical vapor deposition will be described in more detail below. The resulting substrate with the conductive layer coated thereon can be used as a biosensor component, such as an electrode. Such electrodes may include a working electrode, a reference electrode, and / or a counter electrode. In some embodiments, such as when a conductive layer is vacuum-coated on a roll of substrate material via roll-to-roll physical vapor deposition, the resulting film sheet can be cut to an appropriate size to form a thin-film electrode specifically sized for a biosensor component. In other embodiments, the biosensor assembly can be formed from a thin-film sheet by etching, such as chemical or laser etching. In still other embodiments, the biosensor assembly can be formed using a patterned mask placed on a substrate, and a conductive layer can be physically vapor-deposited thereon to form the conductive layer of the biosensor assembly.

[0065] The provision of the target in step (d) may include providing a physical vapor deposition target composed of any of the aforementioned resistive materials. For example, in some embodiments, a thin film amorphous carbon layer is fabricated using a carbon-containing physical vapor deposition target. Such a resistive material target may contain less than about 0.1, 0.05, or 0.001% by weight of incidental impurities. In embodiments, the target may include a material different from the deposited resistive layer material but which generates the resistive material when used as a source material in physical vapor deposition. It should be understood that the resistive material target may have a different composition and / or structure than the deposited resistive material. In some embodiments, the physical vapor deposition target is disposed within and / or contains an electrode, such as a sputtering cathode, during the physical vapor deposition process. In some embodiments, the physical vapor deposition target may be circular with a diameter of at least 2, 4, 8, 12, 16, or 20 cm. In other embodiments, the physical vapor deposition target may be a tubular target with an inner diameter of at least 2, 4, 8, or 16 cm and an outer diameter of 20, 24, 28, or 32 cm. In other embodiments, the physical vapor deposition target may be rectangular with dimensions of 5 to 25 cm in width, 25 to 75 cm in length, and 0.3 to 5 cm in thickness. However, it should be understood that embodiments of this disclosure contemplate the use of targets of other shapes and sizes.

[0066] The physical vapor deposition in step (e) typically involves coating the substrate with material from a resistive material target to form a resistive material layer. As used herein, the term "physical vapor deposition" should refer to the deposition of a thin film by condensing vaporized material onto the substrate. Physical vapor deposition coatings can be achieved using any of the aforementioned types of physical vapor deposition methods, such as sputtering, thermal evaporation, electron beam evaporation, arc vaporization, co-evaporation, ion plating, etc. For example, in some embodiments, the physical vapor deposition step is performed via sputtering, wherein a conductive layer (previously deposited on the substrate) is coated with a resistive material layer by sputtering a resistive material target via a sputtering apparatus. Specific examples of such sputtering-type physical vapor deposition are described in more detail below. The resulting substrate, having a conductive layer and a resistive material layer coated thereon, can be used as a biosensor component, such as an electrode. In embodiments, the "resistive material" layer is typically a layer separate from the conductive layer to form a laminated structure, wherein distinct interfaces exist between the layers so that the resistive material layer and the conductive layer are each separate and discrete layers with different compositions.

[0067] In some embodiments, such as when a conductive layer is vacuum-coated onto a roll of substrate material using roll-to-roll physical vapor deposition, the resulting thin film can be diced to appropriate sizes to form thin-film electrodes specifically sized for the biosensor assembly. Such electrodes may include working electrodes, reference electrodes, and / or counter electrodes. Electrodes may also include those for detecting the conductivity of a sample (whether or not it has been applied to the biosensor assembly), or other electrical properties of the sample or sample environment that can be used with the biosensor. In other embodiments, the biosensor assembly may be formed from the thin film by etching, such as chemical or laser etching. In still other embodiments, the biosensor assembly may be formed using a patterned mask placed on a substrate and a conductive layer, on which a layer of resistive material is physically vapor-deposited to form the biosensor assembly.

[0068] In some specific embodiments, the biosensor assembly can be fabricated via roll-to-roll physical vapor deposition, including roll-to-roll magnetron sputtering. For example, a roll-to-roll magnetron sputtering coater with a 77.50 cm wide roll, such as the Smartweb coater from Applied Materials, Inc. or the Mark80 from CHA Industries, Inc., can be used to sputter a substrate sheet containing a polymer film made of PET (polyethylene terephthalate) with a thickness of 25 µm to 250 µm and a width of 33.02 cm. A conductive layer of a non-precious metal alloy, such as certain nickel-chromium alloys, can be deposited using a single-target or dual-target configuration. A target composed of a non-precious metal alloy plate (such as those available from Tricor Industries, Inc.) can be used. The vacuum chamber of the sputtering coater can be evacuated to at least 10 °C using a combination of diffusion and mechanical pumps. -5The reference pressure of Torr. In other embodiments, a combination of mechanical pumps, turbopumps, cryogenic pumps, and / or oil diffusion pumps can be used. A 2 kW power supply (such as that provided by Advanced Energy Inc.) can be used to supply energy to the magnetron sputtering cathode housing a generally rectangular non-precious metal alloy target. The argon flow into the vacuum chamber can be controlled (e.g., using an MKS Model 1179A flow controller) to set the sputtering pressure of 3 to 10 mTorr used during sputtering.

[0069] The thickness and sheet resistance of the sputtered conductive layer can be effectively controlled in situ by controlling specific process parameters. Examples of process parameters include roll-to-roll speeds (i.e., controlling the speed at which the substrate sheet passes through the vacuum chamber during sputtering), the power supplied to the sputtering target (i.e., the product of voltage and current applied to the plasma formed near the target surface), the gas pressure in the sputtering chamber, and the number of targets present in the chamber. For example, to sputter a conductive layer of a given alloy, the roll speed can be set to 0.1 to 3.5 m / min and the sputtering power density to 1 to 8 W / cm². In an embodiment, a sputtered conductive layer of an alloy with a measured thickness of approximately 25 nm and a sheet resistance of approximately 45 ohms / cm² can be formed.

[0070] A resistive material layer can be deposited over the conductive layer using one of the aforementioned deposition techniques. For example, in one embodiment, a resistive layer can be deposited from a carbon target using DC magnetron sputtering. The thickness of the resistive material layer can be controlled by controlling specific process parameters. Examples of process parameters include roll-to-roll speed (i.e., controlling the speed of the substrate sheet as it passes through the vacuum chamber during sputtering), power supplied to the sputtering target (i.e., the product of voltage and current applied to the plasma formed near the target surface), gas pressure in the sputtering chamber, and the number of targets present in the chamber. For example, in some embodiments, to sputter a conductive layer on a given alloy, the roll-to-roll speed can be set to 0.1 to 3.5 m / min and the sputtering power density to 1 to 8 W / cm². In embodiments, a sputtered resistive layer with a measured thickness of approximately 1–200 nanometers can be formed.

[0071] In addition to the roll-to-roll process described above, large-scale roll-to-roll processes can be used to fabricate biosensor assemblies using scaled-up versions of the same geometry. In such large-scale roll-to-roll processes, the maximum roll speed can be 0.1 to 10 m / min, 3 to 7 m / min, or higher than 10 m / min. Large-scale roll-to-roll processes can provide sputtering power densities of 0.1 to 13, 2 to 10, or 5 to 8 W / cm². Furthermore, the number of targets can include 2, 4, 6, or more, and the roll width of the substrate sheet can be 75 cm or greater.

[0072] Another implementation scheme suggests the use of physical vapor deposition in which the substrate sheet is held fixed in a vacuum chamber. Some such implementation schemes are described in detail below in the Examples section. In some implementation schemes in which the substrate sheet is held fixed, the deposition time for depositing a conductive layer on the substrate sheet can be 5, 10, 15, 30 minutes or longer.

[0073] As described above, biosensor components comprising conductive and resistive material layers formed of non-precious metal alloys, as described herein, can exhibit desirable electrochemical properties that make them particularly suitable as alternatives to biosensor components containing noble metals (such as palladium and / or gold). For example, a biosensor component of an embodiment of this disclosure may include a thin-film electrode formed of a non-precious metal alloy conductive and resistive material layer that exhibits desirable dose-response characteristics when subjected to chronoamperometry testing.

[0074] In various embodiments, the conductive layer may comprise nickel, chromium, and iron (in amounts as discussed above), and the combination of the conductive layer and the resistive material layer may have an oxidation wave voltage (hereinafter referred to as E) of less than 400, or less than 390, or less than 380, or less than 375, or less than 360, or less than 350, or less than 340, or less than 330, or less than 325, or less than 320, or less than 310, or less than 300, or less than 290, or less than 280, or less than 275, or less than 270, or less than 260 millivolts (mV) against the Fe(II)[CN]6 mediator, as determined in a Type I linear sweep voltammetry test (as discussed in the Examples section). 峰值,阳极 ).

[0075] The invention can be further illustrated by the following embodiments of its implementation, although it should be understood that, unless expressly indicated otherwise, these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Example

[0076] Fabrication of thin film electrodes For each of the following embodiments (and comparative examples), a biosensor assembly in the form of a thin-film electrode is formed using the physical vapor deposition method described below. It should be understood that the thin-film electrode can be formed using the methods described below to comprise a conductive layer comprising many different types of elements and elemental alloys, such as the non-noble metal compositions listed in Table 1. In most embodiments, unless otherwise specified, these thin-film electrodes also include a layer of carbon resistive material deposited on the conductive layer. The method includes forming the thin-film electrode film as follows: (a) Deposit metal or metal alloy on a 10.16 cm × 10.16 cm square PET substrate sheet using a DC (“DC”) magnetron sputtering in a high vacuum chamber, using a Denton Vacuum Desktop Pro sputtering apparatus; (b) Evacuate the vacuum chamber to ~10 -5 Torr's initial reference pressure; (c) Introduce 10 sccm of argon gas into the high vacuum chamber to establish a deposition pressure of 4 mTorr; (d) The substrate sheet rotates at approximately 2 revolutions per minute in the vacuum chamber; (e) Hold the 5.08 cm diameter target of the metal or metal alloy under a DC magnetron sputtering apparatus at a constant power of 40 Watts for 15 minutes for deposition time so as to coat at least a portion of the substrate with the conductive layer (in order to initialize the target, hold the target under a DC magnetron sputtering apparatus at a constant power of 40 Watts for 5 minutes for pre-sputtering time before introducing the substrate into the vacuum chamber). (f) After depositing the conductive layer, a carbon layer is subsequently deposited. A 5.08 cm diameter target of graphite material is held under a DC magnetron sputtering apparatus at a constant power of 40 Watts for 15 minutes to coat at least a portion of the conductive layer deposited in step (e) with the carbon layer (to initialize the target, the target is held under a DC magnetron sputtering apparatus at a constant power of 40 Watts for 5 minutes of pre-sputtering before introducing the substrate coated with the conductive layer into the vacuum chamber); and (g) All depositions were carried out at room temperature.

[0077] Individual thin-film electrodes measuring 5.08 cm × 7.62 cm were cut from the thin-film electrode film formed by physical vapor deposition as described above. Electrochemical experiments were conducted using a three-electrode Gamry Instruments Reference 600 potentiostat, which contained the thin-film electrode film housed within a Gamry Instruments VistaShield Faraday Cage. Each thin-film electrode was shaped as a working electrode by masking a portion of electroplated tape with a single 3 mm diameter hole punched therein. Thus, the unmasked portion of the thin-film electrode formed by the punched hole provides a geometric working electrode surface area of ​​0.0707 square centimeters. Another distinct area of ​​the unmasked portion of the thin-film electrode serves as an electrical connection point to the working electrode leads of the potentiostat. The masked portion of the thin-film electrode was placed on a flat support block of a non-conductive material, such as plastic. The thin-film electrode was then placed in the working electrode port of the glass electrochemical cell. The exposed 3 mm diameter portion of the thin-film electrode was positioned near the center of the bottom opening of the working electrode port of the electrochemical cell. The working electrode port of the electrochemical cell was sealed with a clamp and an O-ring. The electrochemical cell also includes a reference electrode containing a saturated calomel reference electrode and a carbon auxiliary electrode. The reference electrode and auxiliary electrode are located at the reference electrode port and auxiliary electrode port, respectively. Furthermore, the reference electrode and auxiliary electrode are connected to the reference lead and auxiliary lead of a potentiometer, respectively. The electrochemical cell also includes a gas flow port, through which the test solution is degassed and covered with an inert gas, such as nitrogen.

[0078] Thin-film electrodes were prepared from nickel-chromium alloys according to the procedure described above, wherein the alloys had Ni:Cr ratios (by weight) of 100:0, 90:10, 85:15, 80:20, 72:28, 60:40, 50:50, 40:60, and 0:100. The thin-film electrodes having these conductive layers also included a carbon resistive layer prepared according to the procedure described above. The thickness of the carbon resistive layer, determined by TEM imaging of a cross-section of the electrode, was approximately 15 nm.

[0079] Description of Type 1 linear sweep voltammetry test The electrochemical response of a thin-film electrode can be tested using a Type 1 linear sweep voltammetry assay. The Type 1 linear sweep voltammetry assay comprises the following steps: placing 50 mL of a 10 mM potassium phosphate buffer solution containing 145 mM sodium chloride at pH 7.1 into the electrochemical cell and sealing the cell with a stopper. Gas inlet and outlet fittings connected to the gas flow port allow for inert gas bubbling (i.e., degassing) of the buffer solution via a nitrogen flow using a mesoporous filter rod. The gas flow port also allows the gas flow to be switched from the filter rod to a headspace overlay configuration. The gas outlet is connected to an oil bubbler to prevent back-diffusion of external gases (e.g., air) into the electrochemical cell. The buffer solution is stirred with a magnetic stir bar for at least 5 minutes while bubbling with nitrogen before switching the gas flow to the overlay configuration. Otherwise, there is no agitation of the buffer solution from bubbling or other sources during the electrochemical experiment conducted by the Type 1 linear sweep voltammetry assay (i.e., the solution remains stationary during the electrochemical test).

[0080] Linear sweep voltammetry was performed on the thin-film electrode, including the working electrode, within the electrochemical cell. The initial voltage potential for linear sweep voltammetry, measured between the working electrode and the reference electrode (i.e., the saturated calomel reference electrode), was 0 V relative to the open-circuit potential (also known as the resting potential). After a resting period of at least 10 seconds before the voltammetric experiment, the voltage potential was scanned at the anodic potential at 25 mV / s until a current of at least 50 µA was observed. For solutions containing the Fe(II)[CN]6 mediator at a concentration of 1 mM, the linear sweep voltammetry conditions were otherwise identical to those for mediator-free solutions.

[0081] Determine the peak voltage of the oxidation wave ("E"). 峰值,阳极 ”, the E 峰值,阳极 Defined as the voltage at which a local maximum current is observed due to the oxidation of electroactive substances in solution, as measured between the working electrode and the counter electrode versus the reference electrode. This is exemplified by the oxidation wave and related E obtained from the thin-film electrode using a type I linear sweep voltammetry assay. 峰值,阳极 The diagram shows Figure 3 From. Figure 3 As can be seen from the data, the measured E, as measured by the reference electrode, is... 峰值,阳极 The (or E-peak) value is approximately -76 mV.

[0082] Applying a type 1 linear scan voltammetry test to a thin film electrode Several different thin-film electrodes were tested using a type 1 linear sweep voltammetry test. More specifically, thin-film electrodes formed from NiCr100:0 (or pure Ni), NiCr 90:10, NiCr 85:15, NiCr 80:20, NiCr 72:28, NiCr 60:40, NiCr 50:50, NiCr 40:60, and NiCr 0:100 (or pure Cr), each (nickel / chromium alloy) covered with a layer of amorphous carbon resistive material, were tested.

[0083] The results of such tests on alloys with 72 to 90 wt% Ni are illustrated in the figure. Figure 4 In general, it is desirable for the thin-film electrodes used in biosensors to exhibit peak anolytic currents of Fe(II)[CN]6 at the lowest possible voltage. It is also generally desirable for the thin-film electrodes used in biosensors to exhibit currents that are minimized and / or reduced under the influence of certain electrode potentials. Figure 4 This is a graph of a type 1 linear sweep voltammetry test performed on various C-based thin-film electrodes on nickel / chromium alloys using phosphate buffer and Fe(II)[CN]6 mediator, and is shown as the voltage at which oxidation of the Fe(II)[CN]6 mediator occurs. Figure 4 The diagram illustrates the heterogeneous electron transfer kinetics of these alloys with Fe(II)[CN]6. Generally, it is desirable for electrode materials in sensors, such as blood glucose sensors, to have the fastest possible heterogeneous electron transfer kinetics so that the applied oxidation voltage required to operate the sensor is as small as possible. In some embodiments, biosensors can operate at a voltage sufficient for the anodic field to control the working electrode current via diffusion of electroactive substances, such as mediators. If the applied voltage is too oxidizing, it may oxidize interfering substances that may be present in the blood, such as uric acid, acetaminophen, etc. This can cause undesirable positive biases in the measured blood glucose concentration and less accurate sensors. Figure 4 The review revealed that, for each of the electrodes shown, the heterogeneous electron transfer kinetics with ferrocyanide were generally acceptable, with NiCr 90:10 and NiCr 72:28 exhibiting faster heterogeneous electron transfer than NiCr 85:15 and NiCr 80:20.

[0084] All thin-film electrodes prepared for each NiCr alloy were tested on three repeating films using a type 1 linear sweep voltammetry test, and the average E was measured for each different NiCr alloy. 峰值,阳极 Values. The results of such tests on alloys with Ni ranging from 0 to 100 wt% are illustrated in... Figure 5 middle. Figure 5 It is the average E 峰值,阳极The graph shows the value as a function of the weight percentage of nickel in the NiCr alloy conductive layer. Ideally, the thin-film electrode for biosensors should exhibit an Et value for Fe(II)[CN]6 at the lowest possible voltage. 峰值,阳极 Electric current. Figure 5 The review revealed that the heterogeneous electron transfer kinetics with ferrocyanide generally improve with increasing chromium content.

[0085] Figure 6 The graphs are from a type 1 linear sweep voltammetry test comparing C on thin-film electrodes of nickel / chromium alloys with 40 wt% nickel and 80 wt% nickel, respectively, using phosphate buffer and Fe(II)[CN]6 mediator. Figure 6 The review revealed that the heterogeneous electron transfer kinetics with ferrocyanide were faster for NiCr alloys containing 40 wt% nickel than for those containing 80 wt% nickel.

[0086] Mechanical Flexibility Analysis Using Mandrel Bending Test with Thin Film Electrodes The mechanical flexibility of different membranes was analyzed using a mandrel bending test. The test membranes were manufactured according to the above procedure, and each membrane comprised a NiCr alloy conductive layer of 40 to 100% by weight of nickel and had a carbon resistive layer.

[0087] Use the following apparatus to perform a mandrel bending test: a. multimeter - Multimeter / ohmmeter capable of measuring resistance to an accuracy of 0.01 ohms b. probe - A resistance probe for measuring the film along its long axis contacts the film at two locations perpendicular to its length, with contacts 2 inches apart covering the full width of the film. c. spindle - Mandrels with diameters of 1 / 8", 1 / 4", 1 / 2", and 5 / 8" and smooth, clean surfaces, and mounted on ball bearings at each end to allow for smooth and easy rotation of the mandrel.

[0088] First, visually inspect the coating to ensure there are no scratches, creases, wrinkles, or torn edges on the coating surface, then perform a mandrel test. Cut the thin-film electrode to be tested into strips 2 inches wide and at least 9 inches long. Take care to avoid any cracks while cutting the film.

[0089] Then the cut membrane was tested as follows: a. Measure and record the initial sheet resistance (Ro) in ohms / sq along the length of the sample using a 2-inch resistance probe, with measurements at 3-inch intervals. b. Then bend the membrane around the 5 / 8" mandrel so that the coated surface contacts the mandrel. c. Simultaneously fix the end of the membrane and apply sufficient tension to the membrane to ensure that the membrane is in contact with the mandrel. d. Carefully apply gentle pressure to the mandrel while rolling the film back and forth to keep it in contact with the coating. Be careful to ensure the film rolls along the mandrel without slipping to avoid scratches. Mark the coating area for testing. e. Step d involves 3 cycles or 6 strokes. f. Measure and record the sheet resistance (R) in ohms / sq along the length of the specimen that contacts the mandrel during the test using a 2-inch resistance probe, with measurements taken at 3-inch intervals on the test area.

[0090] The results of the mandrel test, which compares the final sheet resistance (R) with the initial sheet resistance (R0), are shown in... Figure 7 middle. Figure 7 The review revealed that films with a NiCr alloy conductive layer containing 85 to 100% nickel by weight exhibit lower mechanical stability compared to films with a NiCr alloy conductive layer containing 40 to 80% nickel by weight, especially when using a smaller diameter mandrel. Thin-film electrodes with better relative mechanical integrity, as confirmed by this test, are believed to be more desirable for improved manufacturing robustness using roll-to-roll and sheet-based methods. When comparing the two films using the aforementioned mandrel test, the better-performing film is believed to represent more robust mechanical properties and improved repeatability and consistency for processing and using thin-film electrode films in biosensor applications.

[0091] The detailed description of the embodiments disclosed above is intended to describe various aspects of the invention in sufficient detail to enable those skilled in the art to practice the invention. Other embodiments may be adopted and changes may be made without departing from the scope of the invention. The detailed description above should therefore not be interpreted in a limiting sense. The scope of the invention is defined only by the full scope of the claims set forth in the following formal application and the equivalents to which those claims are entitled.

[0092] In this specification, references to "an embodiment," "an implementation," or "implementation" mean that the mentioned feature is included in at least one embodiment of the technology. Individual references to "an embodiment," "an implementation," or "implementation" in this specification do not necessarily refer to the same embodiment and are not mutually exclusive, unless so specified and / or obvious from the specification to those skilled in the art. For example, features, steps, etc., described in one embodiment may be included in other embodiments, but not necessarily. Therefore, this technology can include various combinations and / or integrations of the embodiments described herein.

[0093] The inventors hereby declare that they intend to rely on the principle of equivalence to determine and assess the reasonable and fair scope of the invention, as it involves any matter (apparatus) that does not materially deviate from the literal scope of the invention as set forth in the following claims.

[0094] definition It should be understood that the following text is not intended to constitute an exclusive list of the terms defined. Other definitions may be provided in the above description, for example, when used in the context of the defined terms.

[0095] The terms “a” and “the” used in this article refer to one or more.

[0096] As used herein, the term “and / or” when applied to a list of two or more items means that any of the listed items may be used alone or in any combination of two or more listed items. For example, if a composition is described as containing components A, B and / or C, the composition may contain only A; only B; only C; both A and B; both A and C; both B and C; or A, B and C.

[0097] As used in this article, the term "contains" is an open transitional term used to transition from a subject listed before the term to one or more elements listed after the term, wherein the elements listed after the transitional term are not necessarily the only elements constituting the subject.

[0098] The term “having” as used in this article has the same open meaning as “containing” as provided above.

[0099] The term “includes” as used in this article has the same open meaning as “includes” as provided above.

[0100] Numerical range This specification uses numerical ranges to quantify certain parameters relevant to the invention. It should be understood that when numerical ranges are provided, these ranges are to be interpreted as literally supporting claim limitations that list only the lower limit of the range and claim limitations that list only the upper limit of the range. For example, a disclosed numerical range of 10 to 100 provides literal support for claims listing "greater than 10" (no upper limit) and claims listing "less than 100" (no lower limit).

Claims

1. A biosensor assembly for analyzing biological samples, the biosensor assembly comprising: Base; A conductive layer deposited on the substrate; A resistive material layer deposited on the conductive layer; and Bioreactants used for electrochemical reactions with the biological samples, The conductive layer is an alloy of nickel and chromium, comprising 5 to 40% by weight nickel, 60 to 95% by weight chromium, and less than 1% by weight of each of the following elements: iron, carbon, sulfur, phosphorus, molybdenum, niobium, cobalt, aluminum, titanium, or boron. The thickness of the resistive material layer is 5-15 nm, and The resistive material layer is amorphous carbon.

2. The biosensor assembly of claim 1, wherein the biosensor assembly includes an electrode, wherein the electrode is a working electrode, a reference electrode, or a counter electrode.

3. The biosensor assembly of claim 1 or 2, wherein the biosensor is a blood glucose sensor.

4. The biosensor assembly according to any one of claims 1-2, wherein the biosensor assembly comprises a test strip.

5. The biosensor assembly of any one of claims 1-2, wherein the substrate has a thickness of 25 to 500 µm and the conductive layer has a thickness of 15 to 200 nm.

6. The biosensor assembly of any one of claims 1-2, wherein the conductive layer is sputtered on the substrate and the resistive material layer is sputtered on the conductive layer.

7. The biosensor assembly of any one of claims 1-2, wherein the substrate comprises a flexible non-conductive membrane.

8. The biosensor assembly according to any one of claims 1-2, wherein the biosensor assembly has a visible light transmittance of no more than 20%.

9. A method for forming an electrode for a biosensor, comprising: (a) Provide a base; (b) Provide a conductive material target; (c) Depositing at least a portion of the substrate using material physical vapor deposition from the conductive material target, thereby forming a conductive layer on the substrate; (d) Provide a resistive material target; and (e) Deposit at least a portion of the conductive layer using material physical vapor deposition from the resistive material target, thereby forming a resistive material layer on the conductive layer; The conductive layer is an alloy of nickel and chromium, comprising 5 to 40 wt% nickel, 60 to 95 wt% chromium, and less than 1 wt% of each of the following elements: iron, carbon, sulfur, phosphorus, molybdenum, niobium, cobalt, aluminum, titanium, or boron. The thickness of the resistive material layer is less than 5-15 nm, and The resistive material layer is amorphous carbon.

10. The method of claim 9, wherein the substrate comprises polyethylene terephthalate (PET), wherein the substrate has a thickness of 25 to 500 µm, the conductive layer has a thickness of 15 to 200 nm, wherein the electrode has a visible light transmittance of no more than 20%, and wherein the biosensor comprises a blood glucose sensor.

Citation Information

Patent Citations

  • Method for forming multi-layer structure

    CN101360849A

  • Biological functional multilayer film modified electrode and method for making same

    CN101393160A

  • Needle amperometric determination type glucose sensor for subcutaneous tissue real-time monitoring and manufacturing method thereof

    CN101530327A

  • Ultrathin film modified electrode with compounded hydrotalcite nanometer slices and double protein, and preparation method thereof

    CN101839884A

  • Electrochemical biosensor structure and measuring method using the same

    CN102187213A